A concurrent engineering framework to explore the servicer-client relationship in on-orbit servicing. - Matos De Carvalho, Tiago (Cranfield University, 2018)
The implementation of On-Orbit Servicing (OOS) in the development and operation of space systems has been pursued to enable inspection, maintenance, repair and assembly of systems in space. Performing such tasks robotically involves the consideration of two sides, a Servicer satellite performing the necessary tasks and a Client satellite receiving it. A critical point for a realistic consideration of OOS demands the concurrent approach of both sides. Despite the current interests towards OOS, there is still a gap in the research into the relationship of Client and Servicer. This research aims to develop and demonstrate a methodology to technically incorporate On-Orbit Servicing, at a system-level, to the mission design process and operation of current and new satellites. The first objective deals with the systematic arrangement of the current available knowledge. A top-down approach is used to provide a taxonomy of servicing, followed by the functional decomposition of the main tasks. This objective clarifies the main issues observed today in OOS, directly related to the Client-Servicer relationship. The second objective is to establish the proposed framework. Agent Based Modelling and Simulation is used to implement the main guidelines and concept of operation, and to output different metrics to allow users (Servicers and/or Clients) to evaluate the attractiveness of various OOS scenarios. The mathematical background for the different metrics is defined and discussed. This is complemented by a solution exploration feature for specific types of OOS. A set of cases is presented based on current interests of operators, providing coverage of potential scenarios to use the framework. The proposed objectives are met, achieving the main research aim. The results help to illustrate the effects of servicing in the systems design and operation. Features of the framework expand the capacity to identify potentially attractive conditions for both sides. Such characteristics are not observed in the current published research and represent a powerful tool to be employed at early stages of design and procurement.
Keywords: On-orbit servicing; relationship approach; concurrent framework; servicer; client; agent based model and simulation